Optimalisasi Edukasi Ekonomi Terapan Untuk Meningkatkan Literasi Finansial Dan Pola Pikir Kemandirian Anak Panti Asuhan - Nicholas Pangkaras; Yustina Novita Wangu; Kartinto Meidiono; Alisha Nabilah Sarifah; Irfan Yusuf (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
This community service program was carried out at the Abdi Agape Orphanage in Pontianak with the aim of improving financial literacy and fostering an economic independence mindset among the children. The background of this activity stems from the low ability to manage pocket money and the lack of basic understanding of personal finance concepts among the orphanage residents. Through an educational and participatory approach, the program was designed in the form of simple financial management training, micro-entrepreneurship practice, and digital promotion training using Canva. Each session focused on direct application in daily life, enabling participants to understand the economic value of their everyday activities. The implementation results showed a significant improvement in participants’ ability to manage personal finances, create budgeting plans, and develop small business initiatives oriented toward independence. Moreover, the program strengthened the children’s sense of responsibility, teamwork, and confidence in making financial decisions. Overall, this participatory-based applied economic education model proved effective in building financial awareness and entrepreneurial spirit among vulnerable groups, and it holds great potential to be developed as a sustainable empowerment strategy in similar institutions.